Assessing the Energy Efficiency of Saudi Arabia's Relatively Middle Eastern Countries in the Context of Sustainable Development Goal Seven (SDG7) - Alam, Teg (International Journal of Energy Economics and Policy, 2024)
This paper employs a non-parametric approach to assess and compare the energy efficiency of Saudi Arabia with that of other Middle Eastern countries in the context of SDG7. An approach for evaluating the performance of each unit that utilizes optimization and linear programming is data envelopment analysis (DEA). A reference set for an inefficient unit is created to facilitate the comparison of various units against the efficiency boundary and enhance the efficiency of each unit. The research employs data envelopment analysis, incorporating three input and two output variables. This approach enables Middle Eastern countries to identify ineffective measures and recall essential actions necessary for enhancement. This study's findings suggest recommendations for the effective utilization of resources. This analysis indicates that Saudi Arabia, along with certain Middle Eastern nations, exhibits greater energy efficiency than most countries in the region. When analyzing the Middle East, Saudi Arabia, United Arab Emirates, Bahrain, Cyprus, Qatar, and Turkiye are notable examples of sustainable practices requiring further investigation. Furthermore, Yemen, Lebanon, and Syria require additional scrutiny to enhance effectiveness. The proposed study presents noteworthy conclusions concerning energy efficiency. The findings are anticipated to aid government agencies in pinpointing the factors influencing sustainable development and facilitating policymaking in Middle Eastern countries.